Hubungan Intensitas Paparan Bising Dan Masa Kerja Dengan Gangguan Pendengaran Pada Karyawan PT. X - Marisdayana, Rara; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Noise exposure can cause hearing loss types of conductive hearing loss, sensorineural hearing loss or deafness mix. Noise exposure in  the long term and exceeds the NAB may cause damage to the cochlea which will result in sensorineural deafness. Conductive hearing loss caused by exposure to noise intensity that occur within a short time can cause trauma to the outer ear to the eardrum and middle ear. This was an observational cross sectional design. The sample in this study were employees of PT. X with inclusion criteria. Collecting data using tools such as questionnaires and for hearing loss was measured using a audiometer. The results by Chi-Square test showed significant relation between noise exposure with hearing loss (p = 0.001; PR 2.7 (95%CI : 1.3-5.2) Have a significant relationship between the period of work with hearing loss (p = 0.000; PR 3.3 (95%CI : 1.9-5.9). The stratification analyze can be conclude variables ear disease history, period of work, family history, age it’s not counfounding, whereas length of employment it’s counfounding to the noise exposure and hearing loss as well as increase the risk of hearing loss. Noise exposure and period of work is risk factor for the hearing loss in PT.  X